TEACHING WRITING EXPLANATION TEXT THROUGH COMBINING BRAINSTORMING AND KNOW-WANT-LEARN (KWL) CHART STRATEGIES TO THE ELEVENTH GRADE OF VOCATIONAL INDO HEALTH SCHOOL PALEMBANG - Rinda Dwi Shintia (Universitas PGRI Palembang, 2021)
The objective of this study was to find out whether or not there is any significant difference on Students’ Achievement in Writing Explanation Text to the Eleventh Grade of Vocational Indo Health School Palembang who are taught through Combining Brainstorming and Know-Want-Learn (KWL) Chart strategies and those who are not. This study used quasi-experimental method with non-equivalen control group design. The population of this study was all of the eleventh grade of Vocational Indo Health School Palembang. The sample was 20 students , 10 students in experimental group from XI Nurshing class and 10 students in control group from XI Medical Laboratory class. In the collecting data, a written test of explanation text was used, and to answer the problem of this thesis the data were analyzed by using Independent sample test in SPSS 23 Computer program. The result of this study showed that in the experimental group, mean was 70.90. Meanwhile, in the control group, and the mean was 66.70. On the other hand, the result of t-obtained was 2.412. Meanwhile, its critical value at 0.05 significant level for two tailed with 18(df) was 2.100. Since the t-obtained was higher than t-table, Ho was rejected and Ha was accepted. As a final result, the combination Brainstorming and Know-Want Learn (KWL) Chart Strategies made a significant difference on students’ achievement in writing explanation text to the eleveth grade of Vocational Indo Health School Palembang who were taught through combining brainstorming and know-want-learn (kwl) chart strategies and those who were not.